Comparative study of two methods for rare earth elements analysis in human urine samples using inductively coupled plasma-mass spectrometry - Brouziotis, Antonios Apostolos; Giarra, Antonella; Marano, Alessandra; Di Nunzio, Aldo; Lombardo, Francesco; Guida, Marco; Libralato, Giovanni; Trifuoggi, Marco (Frontiers in Environmental Science, 2022)
The application of rare earth elements (REEs) in several areas, including high-tech technology, agriculture, medicine, and fuels, has made them an essential component of our everyday life. This extensive use of REEs in several technologies is expected to potentially impact human health. Even if several studies investigated the levels of REEs in human matrices, until now no standard method has been established for analyzing these elements in human matrices. The sample analysis should be of high quality and the methods should be validated properly to ensure quality of the procedure and traceability of the analytical data. In this research, we compared the validation and effectiveness of two different methods of sample preparation for human urine samples: a simple dilution of the sample (DIL) was compared with microwave assisted-acid decomposition (MIN) for tracing REEs levels in human urine samples. The analysis was carried out by inductively coupled plasma mass spectrometry (ICP-MS). The working conditions have been set in high sensitivity mode. Accuracy of the proposed method was evaluated by spiking the sample matrix with known concentrations of analyte standards. Both methods showed adequate precision of repeatability and intra-laboratory reproducibility, with the DIL method showing better precision of both repeatability and reproducibility than the MIN method. The CVr% values of repeatability range from 1.5 to 12% for the DIL and from 8.4 to 16% for the MIN method. The CVr% values of reproducibility range 6.2 to 23% for the DIL and from 8.6 to 24% for the MIN method. REE recoveries for both methods were very close to 100%. Both methods proved to be effective for the determination of REE levels in human urine matrices.